Genetic and clinical analysis of TP73 gene in amyotrophic lateral sclerosis patients from Chinese mainland - Tang, Xuxiong; Yuan, Yanchun; Liu, Zhen; Bu, Yue; Tang, Linxin; Zhao, Qianqian; Jiao, Bin; Guo, Jifeng; Shen, Lu; Jiang, Hong; Tang, Beisha; Wang, Junling (Frontiers in Aging Neuroscience, 2023)
Introduction TP73 was recently identified as a novel causative gene for amyotrophic lateral sclerosis (ALS). We aimed to determine the contribution of variations in TP73 in the Chinese ALS population and to further explore the genotype-phenotype correlations. Methods We screened rare, putative pathogenic TP73 mutations in a large Chinese ALS cohort and performed association analysis of both rare and common TP73 variations between cases and controls. Results Of the 985 ALS patients studied, six rare, heterozygous putative pathogenic variants in TP73 were identified among six unrelated sALS patients. Exon 14 of TP73 might be a mutant hotspot in our cohort. Patients with ALS with only rare, putative pathogenic TP73 mutations exhibited a characteristic clinical profile. Patients harboring multiple mutations in TP73 and other ALS-related genes displayed a significantly earlier onset of ALS. Association analysis revealed that rare TP73 variants in the untranslated regions (UTRs) were enriched among ALS patients; meanwhile, two common variants in the exon-intron boundary were discovered to be associated with ALS. Discussion We demonstrate that TP73 variations also have contributed to ALS in the Asian population and broaden the genotypic and phenotypic spectrum of TP73 variants in the ALS-frontotemporal dementia (FTD) spectrum. Furthermore, our findings first suggest that TP73 is not only a causative gene, but also exerts a disease-modifying effect. These results may contribute to a better understanding of the molecular mechanism of ALS.